Nona Nenovska, Gouvernance des biens communs et spécificités du rapport social à la nature en Bulgarie : le cas de l’aire marine protégée de Kaliakra - Nona Nenovska (Revue de la Régulation)
This thesis studies the local governance of the Kalikara Marine Protected Area, on the Bulgarian Black Sea coast. The main focus of this research is on the formal/informal institutional arrangements for this area. Although formal institutions are important in setting the rules for natural resource governance, this study finds that informal institutions, specific to the country historical and cultural context, tend to shape the outcomes and objectives of this governance and reflect the socio-economic characteristics of the macro-context in which it takes place.